Relationship between mean square errors and wheat grain yields in long-term experiments. (28th May 2017) - Raun, W.; Golden, M.; Dhillon, J.; Aliddeki, D.; Driver, E.; Ervin, S.; Diaite-Koumba, M.; Jones, B.; Lasquites, J.; Figueiredo, B.; Del Corso, M. Ramos; Remondet, N.; et al.
ABSTRACT: When yield data from field experiments are combined, the impact of environment on treatment is ignored. The objectives of this work were to determine the frequency for combining year-to-year data. Grain yield mean square errors (MSE) were calculated by-year from two long-term winter wheat experiments (E222 and E502). These trials have been continuously planted to winter wheat (Triticum aestivum L), and both annually receive different nitrogen (N), phosphorus (P) and potassium (K) fertilizer rates. Relationships between average grain yields, coefficients of variation (CV), and MSE were evaluated over 42 and 41 years for E222 and E502, respectively. The F-statistics (large MSE/small MSE, 39 dfn, 39 dfd, alpha = 0.10) computed from 2 and 3 consecutive years were consistently more than the minimum F-value required to combine sites. For 83 site years of data, combining any 2 or 3 consecutive year periods was not advisable. Individual years should be analyzed and reported on independently.